MARKET ETHICS IN THE DIGITAL ERA: A CRITICAL REVIEW OF MSME MARKETING STRATEGIES AND THE CHALLENGES OF THE PLATFORM ECONOMY THE TITLE IS BRIEF, CLEAR, AND EXPLICIT - Husriadi, Muh. (Laboratorium Riset Ekonomi, 2025)
The development of the platform economy has transformed MSME marketing strategies, but platform dominance often limits the freedom of MSMEs to implement digital marketing ethics. This study aims to examine ethical awareness, ethical challenges, and interactions among coffee MSMEs. Shops with a platform economy in digital marketing practices. The research method uses a qualitative approach with in-depth interviews and observations of coffee MSMEs. shop in Mandonga District. The rresults of the study indicate that MSMEs have a high awareness of the principles of honesty and transparency, but face competitive pressures that encourage them to manage marketing strategies to remain ethical. Dependence on digital platforms limits the space for freedom in marketing strategies, so policy support and ethics training are urgently needed. The implications of this study emphasize the importance of regulation and fostering digital marketing ethics as a requirement for the sustainability of MSME businesses in the competitive digital era. This research provides theoretical and practical contributions in developing an ethical and sustainable digital marketing paradigm.